PENCEGAHAN TINDAK KEKERASAN TERHADAP PEREMPUAN DAN ANAK DI LINGKUNGAN KELUARGA YANG ADA DI DESA WILULANG CIREBON JAWA BARAT - Alwie Al Ghofar; Nur Rahman; Omang Suparman (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2022)
Abstract Indonesia is a state of law, as stipulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. As a state of law, human rights are the main elements that must be protected, enforced and fulfilled by the state. The state has an obligation to guarantee the rights of women and children in Indonesia, which is the quality of the nation's successor. This research activity was carried out in Wilulang Village, Susukan Lebak District, Cirebon Regency, or often also referred to as the East Cirebon region. This activity, as a series of preparations for Wilulang Village, which represents Cirebon Regency in a village competition at the West Java Province level on Increasing the Role of Women Towards Healthy and Prosperous Families (P2WKSS). Domestic violence is a violation of human rights and a crime against human dignity and a form of discrimination that must be eliminated. Article 1 paragraph 1 of Law No. 23 of 2004 concerning the Elimination of Domestic Violence. Efforts to prevent and or overcome various violent behaviors experienced by women and children must receive serious attention and handling. Therefore, the approach in dealing with this problem must be integrated, where in addition to the legal approach one must also consider non-legal approaches which are precisely the causes of violence. By increasing women's awareness of their rights and obligations under the law, increasing public awareness of the importance of efforts to overcome violence against women and children. Keywords: Law, Women and Children, Violence